Clinical application of DA-8902 (Ensure Plus) in oral surgery - SUGAWARA, Toshio; TAKADA, Kazuaki; SAKUTA, Masayoshi; KIRITA, Tadaaki; SUGIMURA, Masahito; MORITA, Nobuo; SAKAMOTO, Tadayuki; SAKAMOTO, Tomoji; NOMA, Hiroyasu; MICHI, Kenichi; KURIHARA, Yukio; WAKUMOTO, Masahiko (Japanese Journal of Oral and Maxillofacial Surgery, 1990)
In the field of oral surgery, since most symptoms appear in and around the oral cavity, tube feeding is frequently carried out for nutritional control. In the present study, we examined the nutritional effects and the safety of Ensure Plus application in 126 cases. As the result, increased rapid turnover protein and nutritional index were found during the application period.Besides, side effects as diarrhea were observed only in 12 patients (9.7%). The application of Ensure Plus in the oral surgery seems to be an easy and effective diet without causing serious side effects. It has been confirmed that Ensure Plus is a superior product.